Codon reassignment and amino acid composition in hemichordate mitochondria - Castresana, Jose (The National Academy of Sciences, 1998)
In the mitochondrial genome of the hemichordate Balanoglossus carnosus, the codon AAA, which is assigned to lysine in most metazoans but to asparagine in echinoderms, is absent. Furthermore, the lysine tRNA gene carries an anticodon substitution that renders its gene product unable to decode AAA codons, whereas the asparagine tRNA gene has not changed to encode a tRNA with the ability to recognize AAA codons. Thus, the hemichordate mitochondrial genome can be regarded as an intermediate in the process of reassignment of mitochondrial AAA codons, where most metazoans represent the ancestral situation and the echinoderms the derived situation. This lends support to the codon capture hypothesis. We also show that the reassignment of the AAA codon is associated with a reduction in the relative abundance of lysine residues in mitochondrial proteins.